MYCN and the epigenome - He, Stanley; Liu, Zhihui; Oh, Doo-Yi; Thiele, Carol J. (Frontiers in Oncology, 2013)
It is well known that Neuroblastoma (NB) patients whose tumors have an undifferentiated histology and a transcriptome enriched in cell cycle genes have a worse prognosis. This contrasts with the good prognoses of patients whose tumors have histologic evidence of differentiation and a transcriptome enriched in differentiation genes. Tumor cell lines from poor prognosis, high risk patients contain a number of genetic alterations, including amplification of MYCN, 1pLOH and unbalanced 11q or gains of Chr 17 and 7, and exhibit uncontrolled growth and an undifferentiated phenotype in in vitro culture. Yet treatment of such NB cell lines with retinoic acid results in growth control and induction of differentiation. This indicates that the signaling pathways that regulate cell growth and differentiation are not functionally lost but dysregulated. Agents such as retinoic acid normalize the signaling pathways and impose growth control and induction of differentiation. Recent studies in embryonic stem cells indicate that Polycomb Repressor Complex proteins (PRC1 & PRC2) play a major role in regulating stem cell lineage specification and coordinating the shift from a transcriptome that supports self-renewal or growth to one that specifies lineage and controls growth. We have shown that in NB, the PRC2 complex is elevated in undifferentiated NB tumors and functions to suppress a number of tumor suppressor genes. This study will review the role of MYC genes in regulating the epigenome in normal development and explore how this role may be altered during tumorigenesis.